Empowering Librarians through Collaboration: Demonstrating Value - Jan Mohamad, Radia Banu; Che Jaafar, Cik Ramlah; Wan Jan, Noor Azlinda; Fesal, Fujica Azura (2018)
Academic libraries and librarians have always been involved in some kind of collaboration within the campus communities since ages. With the advent of technologies combined with violent funding crisis and perception of relevance battles, academic libraries are trying their best to demonstrate value to their campus community to stay afloat. This paper discusses the opportunities available for libraries and librarians to enhance their faculties and empower the librarians through creative collaboration in the areas of research and learning support; scholarly communication activities and research data management to ensure the sustainability and relevance of the institution and the profession.